Exploring the Relationship between Doctors’ Emotional Intelligence and Patient Satisfaction: An Empirical Analysis - Gill, M; Gill, MS; Totala, S (International Journal of Computer Sciences and Engineering, 2025)
Some doctors seem more successful in building trust and satisfying relationship with their patients as compared to others. Emotional Intelligence (EI) may account for this variation. Emotional intelligence refers to an individual’s ability to recognize, monitor, and regulate one’s own and others feelings and emotions, to differentiate among them, and to use this information to guide one's thinking and action. Majority of complaints about doctors relate to poor communication and behaviour, and not clinical competence. Emotional intelligence can possibly fill this gap as an ability to read and manage patient’s emotions. It can improve communication and behaviour which might enhance the patient-doctor relationship, resulting into increased level of patient satisfaction. The present paper empirically explores the relationship between doctor’s emotional intelligence and patient satisfaction with the help of correlation and independent samples t-test analysis.